STRATA NORMS AND SOCIO-CULTURAL SETTINGS IN THE POETRY ANTHOLOGY MOTHER AND THE COFFEE BLOOD OF SOLDIERS BY RAHMAT HELDY HS IN THE IMPLEMENTATION OF LEARNING AT SCHOOL - Sakinah, Nana; Anggraini, Nori; Goziyah, Goziyah (Jurnal Dinamika UMT, 2023)
From the norm stratum analysis, it can be seen that the Anthology of Mother Poems and Blood Coffee of Soldiers by Rahmat Heldy HS, is a medium of enlightenment created by him for all people in order to provide goodness as a legacy for children and grandchildren who will replace the current generation in the future. Any problems that occur in this beloved country should not need to be resolved with bloodshed, disputes and selfishness. As a country that has faith and law, in every problem it faces, it always clings to God because what happens is God's will. If the law of this country cannot solve a problem then leave everything to the fairest law, namely the law of the hereafter. The socio-cultural setting is also found in several poems created by the poet related to the situation and conditions in an area in Indonesia, namely Banten province. Telling the story of Cilegon city, Sawarna village, Binuangeun village, Lebak regency whose lives are very concerning because the officials who are the objects in the poet's poems are described as busy with good names by building caring characters in the community but ignoring the actual situation. In addition, the socio-cultural setting in the poetry anthology Ibu and Darah Kopi Para Serdadu is still very thick with sultanate culture as it is known that the previous sultans were very noble in the eyes of the Banten people because of their love for the community not because of their love for positions and power.